Design of a battery-ultracapacitor hybrid energy-storage system with power flow control for an electric vehicle - Tan B.K.; Tan N.M.L.; Ramasamy A.K. (Institute of Advanced Engineering and Science, 2023)
A combination of battery and ultracapacitor as a hybrid energy storage system (HESS) for an electric vehicle (EV) can result in better acceleration performance, reduced battery charge-discharge cycle and longer driving range. This paper presents a new converter design combining triple-half-bridge (THB) and boost half-bridge (BHB) converters in a battery-ultracapacitor HESS. The BHB converter is used to compensate the voltage variation of the ultracapacitor. A power management system is proposed to control the power of battery and ultracapacitor, to supply the demanded power of an EV. This paper describes the operation of the proposed converter using a simplified ?-type primary-referred equivalent circuit. This paper also shows the simulation results verifying the fast dynamic response of the proposed power management system for the proposed HESS, with minimal current stress. 2018 Institute of Advanced Engineering and Science. All rights reserved.